How PI3K-derived lipids control cell division - Campa, Carlo C.; Martini, Miriam; De Santis, Maria C.; Hirsch, Emilio (Frontiers in Cell and Developmental Biology, 2015)
To succeed in cell division, intense cytoskeletal and membrane remodeling are required to allow accurate chromosome segregation and cytoplasm partitioning. Spatial restriction of the actin dynamics and vesicle trafficking define the cell symmetry and equivalent membrane scission events, respectively. Protein complexes coordinating mitosis are recruited to membrane microdomains characterized by the presence of the phosphatidylinositol lipid members (PtdIns), like PtdIns(3,4,5)P3, PtdIns(4,5)P2 and PtdIns(3)P. These PtdIns represent a minor component of cell membranes, defining membrane domain identity, ultimately controlling cytoskeleton and membrane dynamics during mitosis. The coordinated presence of PtdIns(3,4,5)P3 at the cell poles and PtdIns(4,5)P2 at the cleavage furrow controls the polarity of the actin cytoskeleton leading to symmetrical cell division. In the endosomal compartment, the trafficking of PtdIns(3)P positive vesicles allows the recruitment of the protein machinery required for the abscission.